Proceedings of the XXXIII Brazilian Symposium on Software Engineering 2019
DOI: 10.1145/3350768.3350788
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Textual Issues

Abstract: Recently, GitHub introduced a new social feature, named reactions, which are "pictorial characters" similar to emoji symbols widely used nowadays in text-based communications. Particularly, GitHub users can use a pre-defined set of such symbols to react to issues and pull requests. However, little is known about the real usage and impact of GitHub reactions. In this paper, we analyze the reactions provided by developers to more than 2.5 million issues and 9.7 million issue comments, in order to answer an exten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Potential reasoning may be related to the findings observed in the context of issue reports. Prior work (Borges et al, 2019) reported that issues with reactions usually take more time to be handled and have longer discussions, especially for those complex bugs and enhancements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential reasoning may be related to the findings observed in the context of issue reports. Prior work (Borges et al, 2019) reported that issues with reactions usually take more time to be handled and have longer discussions, especially for those complex bugs and enhancements.…”
Section: Discussionmentioning
confidence: 99%
“…Herring and Dainas (2020) pointed out that females use emoji and emoticons more frequently than males do. Borges et al (2019) explored the usage of GitHub reactions in issues reports. They found that the usage of emoji reactions is increasingly growing and furthermore emoji reactions make more discussion for bug and enhancement issue reports.…”
Section: Modern Communication In Software Developmentmentioning
confidence: 99%